2005
DOI: 10.1111/j.1440-1681.2005.04273.x
|View full text |Cite
|
Sign up to set email alerts
|

Cooling‐induced contraction of the rat gastric fundus: Mediation via transient receptor potential (TRP) cation channel TRPM8 receptor and Rho‐kinase activation

Abstract: 1. Cooling has been shown to induce contractions of several smooth muscles in vitro. However, the mechanism involved in the response is not yet known. In the present study, we investigated the possible involvement of transient receptor potential (TRP) cation channel TRPM8 receptors and the Rho-kinase pathway in cooling-induced contraction of the rat fundus. 2. Cooling-induced contractions were inversely proportional to temperature. Contractions were significantly reduced (by 65.6 +/- 2.4%; P < 0.05) in a Ca2+-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 34 publications
1
37
0
3
Order By: Relevance
“…However, the expression and role of TRPM8 in the GI tract and its involvement in the clinical effects of herbal medicines are still controversial. TRPM8 mRNA was detected in the fundus (and colon) of rat and was implicated in cooling-induced contractions of fundic muscle strips (Mustafa and Oriowo, 2005). Zhang et al also found TRPM8 mRNA in murine NG, small intestinal and stomach mucosa but Penuelas et al failed to confirm its expression although the same primer pairs were used (Zhang et al, 2004;Penuelas et al, 2007).…”
Section: Trpm Channelsmentioning
confidence: 95%
“…However, the expression and role of TRPM8 in the GI tract and its involvement in the clinical effects of herbal medicines are still controversial. TRPM8 mRNA was detected in the fundus (and colon) of rat and was implicated in cooling-induced contractions of fundic muscle strips (Mustafa and Oriowo, 2005). Zhang et al also found TRPM8 mRNA in murine NG, small intestinal and stomach mucosa but Penuelas et al failed to confirm its expression although the same primer pairs were used (Zhang et al, 2004;Penuelas et al, 2007).…”
Section: Trpm Channelsmentioning
confidence: 95%
“…It has been reported that TRPM8 mRNA or protein or both are expressed in the prostate, sensory neurons, gastric fundus, vascular smooth muscle, liver and urogenital organs [19,30,31,32,33]. Several reports have indicated that TRPM8 is expressed not only in the plasma membrane, but also in the endoplasmic reticulum membrane.…”
Section: Discussionmentioning
confidence: 99%
“…34 Antagonizing ROCK using fasudil lowers blood pressure in hypertensive patients. 35,36 Mustafa et al 9 reported that TRPM8-induced gastric fundus contraction is associated with the RhoA/ROCK pathway. Although menthol can inhibit the vasoconstriction by blocking L-type calcium channel-induced calcium influx at several vessel beds, 30 it remains to be determined whether menthol has an effect on calcium release from SR and its underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…7 Johnson et al 8 demonstrated that menthol-induced TRPM8 activation regulates vascular tone. Mustafa et al 9 reported…”
mentioning
confidence: 99%